C. P. E. Bach, Silbermann, and Friederici: Materiality in Galant and Classical Clavichord Music - Proehl, Blake; Beghin, Tom; Koslovsky, John (Ghent Orpheus Instituut, 2028)
C. P. E. Bach’s fabled Silbermann clavichord is perhaps his best-known instrument, but another deserves consideration for its impact on his musical output: a clavichord by Friederici. At this newer instrument, Bach composed his nearly twenty years’ worth of Hamburg works. This clavichord updated Bach’s musical medium to the latest technologies, yet his older instrument was retained and still showcased to visitors. This research project seeks the significance of Bach’s Friederici clavichord and investigates how its affordances differed from those of the Silbermann. As I examine compositions by Bach and contemporaries, I will use enactment and embodiment to glean insights in Bach’s entanglements with his instruments and will engage in empirical measurements of clavichords to understand performer-instrument interaction. Deepening the understanding of the differences between two types of clavichords and their respective roles alongside the rising fortepiano will broaden the clavichord’s influence in our perception of Galant and Classical repertoire.
2028-06-01
FRIS
1
Keywords: Declassifying the Classics: Rhetoric, Technology, and Performance, 1750-1850; Historically informed performance; Clavichord